The Escherichia coli σ(E)-dependent extracytoplasmic stress response is controlled by the regulated proteolysis of an anti-σ factor - Ades, Sarah E. (Cold Spring Harbor Laboratory Press, 1999)
The activity of the stress-responsive σ factor, σ(E), is induced by the extracytoplasmic accumulation of misfolded or unfolded protein. The inner membrane protein RseA is the central regulatory molecule in this signal transduction cascade and acts as a σ(E)-specific anti-σ factor. Here we show that σ(E) activity is primarily determined by the ratio of RseA to σ(E). RseA is rapidly degraded in response to extracytoplasmic stress, leading to an increase in the free pool of σ(E) and initiation of the stress response. We present evidence that the putative inner membrane serine protease, DegS, is responsible for this regulated degradation of RseA.